Current Concepts in Gender-Affirming Surgery Postgraduate Training - Alexander N. Khouri; Caleb Haley; Mark MacEachern; Shane D. Morrison (Indian Journal of Plastic Surgery)
Background Recent advocacy efforts and expanded insurance coverage has increased health care utilization among transgender patients. Therefore, it is pivotal that surgical residents are properly trained to care for transgender patients in both clinical and surgical settings. Yet, no formal curriculum or training requirements exist for surgical residents. The aim of this systematic review is to understand the surgical trainee's postgraduate education and training with respect to transgender health and gender-affirming surgeries (GAS). Methods A Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA)-compliant literature search was performed on December 04, 2020 in PubMed, Elsevier Embase, and Wiley Cochrane Central Register of Controlled Trials. The retrieved hits were screened and reviewed by two independent reviewers. Results Our literature search identified 186 unique publications, of which 14 surveys and one interventional study from various surgical specialties including plastic surgery, urology, otolaryngology, oral and maxillofacial surgery (OMS), dermatology, and obstetrics and gynecology (OBGYN) were included in this study. The majority of residents and program directors in surgical specialties believe education related to transgender health is important, and the current exposure in surgical training does not sufficiently prepare surgical residents to care for this marginalized population. Conclusion Current postgraduate surgical training in gender-affirming surgery is nonuniform across surgical specialty, geographical region, and individual program. Incorporating training modules and hands-on experiences into surgical trainee education will better prepare residents for the numerous clinical and surgical interactions with transgender patients. Further research is required to better understand how to best incorporate these experiences into existing surgical curriculums.